A high yield synthesis of phenytoin and related compounds using microwave activation - Gbaguidi, A.Fernand; KPOVIESSI, Salomé S. D.; Kapanda, Coco N.; Muccioli, Giulio G.; Lambert, Didier M.; Accrombessi, Georges C.; MOUDACHIROU, MANSOUROU; Poupaert, Jacques H. (My University, 2011)
A reaction system is described to synthesize phenytoin, a major antiepileptic drug, and structurally related compounds using a two-step approach. The first step involves the treatment of a benzil derivative by thiourea in dimethylsulfoxide (DMSO) in aqueous KOH under microwave activation. The resulting 2-thiohydantoin was then oxidized to the corresponding hydantoin using perhydrol in dimethylformamide (DMF) in acetic acid. Both steps proceeded in high yield. For example, with this method, phenytoin was obtained in 80% yield while by the conventional Biltz’s method, the yield rarely exceeded 50%. The first step can be advantageously performed using microwave activation. Our process is based on a mechanistic approach supported by theoretical PM3 calculations.
Keywords: Phenytoin; antiepileptic drug; 2-thiohydantoin; Biltz’s method